Sosialisasi Pemanfaatan Air Tanah Untuk Lahan Pertanian dengan Metode JIAT Daerah Pallantikang, Kabupaten Bantaeng - Adi Tonggiroh; Bahrul Hidayah; Baso rezki maulana; Adi Maulana; andi muhammad imran; Asri jaya; Meutia Farida; Jamal Rauf Husein; Rohaya Langkoke; Ratna Husain; Sultan -; Hendra Pachri; Syafruddin -; Muhammad Sulhuzair Burhanuddin (Faculty of Engineering UNHAS, 2020)
Water as a natural resource is the most important part for humans to continue their life. One example of the vital role of water resources for human activities is to fulfill food through agriculture and plantations. The availability of water needs for agricultural productivity is certainly an important study to maintain supply capacity and avoid crises in agricultural and plantation foodstuffs. As mandated by the Water Resources Law, the utilization of water resources is aimed at sustainably utilizing water resources by prioritizing the fulfillment of the basic needs of the community fairly. For the sake of the continuity of human life, water resources must be managed properly by paying attention to and protecting the environment. Almost not all the agricultural and plantation areas in the Planting area have irrigation channels that utilize surface water. Consequently, agricultural production does not reach maximum results, because its water needs are very dependent on rainwater. On the other hand, even though there is an irrigation network, there are areas where the availability of water is not sufficient, so that farming activities of farmers cannot get maximum results. This limitation causes farmers to depend on surface water supply, especially during the rainy season so that problems such as prolonged drought can have fatal consequences. One of the efforts to improve agricultural irrigation is to create a groundwater irrigation network by taking water from bore wells.